أنواع المشروع المشترك - الموسوي علي فوزي; حسين ايمان حمزة (Journal of Legal Sciences, 2019)
Trade relations have witnessed notable development in the last two centuries. reflected its impact on various aspects of economic , social and legal life , the joint venture is one of the type that defined the international trade cooperation and internal cooperation both , and through strategic planner puts a range of different possibilities and specialization in the work according to a certain organization , through the contribution of more than a natural or legal person in the establishment of an independent project working to achieve specific objectives need to be completed include various efforts in the sum of one monolithic . And also considered a joint venture of the most important means of financing for various projects that are appropriate to the prevailing circumstance as it is based on the parties to an agreement under which one or more share in the establishment of a specific project is subject to joint control and reflected the common ownership or partial each party to achieve a certain profit . The joint venture will take one of two formulas: the first joint venture contract is a contract concluded between two or more parties to implement a specific project within a certain period, the second formula are the joint venture organization is the kind of project that take the form of a company with the independence and have an independent judicial personality of the founding parties.